Purification of the yeast U4/U6⋅U5 small nuclear ribonucleoprotein particle and identification of its proteins - Stevens, Scott W. (The National Academy of Sciences, 1999)
The yeast U4/U6⋅U5 pre-mRNA splicing small nuclear ribonucleoprotein (snRNP) is a 25S small nuclear ribonucleoprotein particle similar in size, composition, and morphology to its counterpart in human cells. The yeast U4/U6⋅U5 snRNP complex has been purified to near homogeneity by affinity chromatography and preparative glycerol gradient sedimentation. We show that there are at least 24 proteins stably associated with this particle and performed mass spectrometry microsequencing to determine their identities. In addition to the seven canonical core Sm proteins, there are a set of U6 snRNP specific Sm proteins, eight previously described U4/U6⋅U5 snRNP proteins, and four novel proteins. Two of the novel proteins have likely RNA binding properties, one has been implicated in the cell cycle, and one has no identifiable sequence homologues or functional motifs. The purification of the low abundance U4/U6⋅U5 snRNP from yeast and the powerful sequencing methodologies using small amounts of protein make possible the rapid identification of novel and previously unidentified components of large, low-abundance macromolecular machines from any genetically manipulable organism.